2003
DOI: 10.1002/chin.200308120
|View full text |Cite
|
Sign up to set email alerts
|

New 6‐(4‐Bromophenyl)‐imidazo[2,1‐b]thiazole Derivatives: Synthesis and Antimicrobial Activity.

Abstract: New 6-(4-Bromophenyl)-imidazo[2,1-b]thiazole Derivatives: Synthesis and Antimicrobial Activity. -Based on a recent study a novel set of antibacterial compounds such as (III) and (V) are prepared. Among all (Vd) is the most potent derivative. The biological results are discussed. -(ULUSOY*, N.; KIRAZ, M.; KUECUEKBASMACI, O.; Monatsh. Chem. 133 (2002) 10, 1305-1315; Dep. Pharm. Chem., Fac. Pharm., Univ. Istanbul, Beyazit, TR-34452 Istanbul, Turk.; Eng.) -K. Schneider 08-120

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In continuation of our previous studies on the biological properties of imidazo [2,1-b]thiazole derivatives, [21][22][23][24][25][26][27] in this study, we reported the antibacterial, antitubercular and antiviral activity evaluation of some arylidenehydrazide derivatives bearing imidazo [2,1-b]thiazole moiety. …”
Section: Introductionmentioning
confidence: 71%
“…In continuation of our previous studies on the biological properties of imidazo [2,1-b]thiazole derivatives, [21][22][23][24][25][26][27] in this study, we reported the antibacterial, antitubercular and antiviral activity evaluation of some arylidenehydrazide derivatives bearing imidazo [2,1-b]thiazole moiety. …”
Section: Introductionmentioning
confidence: 71%
“…These effects limit significantly application of some drugs and lead to the development of novel drugs. Thiazole derivatives have attracted the interest of medicinal chemists due to a variety of their biological activities including antibacterial, anti-fungal, anti-HIV, anti-hypertension, anti-inflammatory, anti-cancer, anti-convulsive and anti-depressant [5][6][7][8][9][10]. The mechanisms of 1,3-thiazole derivatives antitumor activity may be associated with DNA intercalation [11,12], PRL-3, SHP-2 and JSP-1 inhibition [13][14][15][16], tumor necrosis factor (TNFα) [17], anti-apoptotic bio-complex Bcl-XL-BH3 [18], integrin avb3 [19], others.…”
Section: Introductionmentioning
confidence: 99%
“…The 2-amino-1,3-thiazoles are biologically important compounds with a wide range of medicinal and biological applications including antibacterial, antifungal, anti-HIV, anti-hypertension, antiinflammatory, anticancer, anticonvulsant, and antidepressant [1][2][3][4][5][6]. Some 2-amino-1,3-thiazole derivatives have been reported as ligands of thrombopoietin [7,8], neuropeptide Y5 [9] and adenosine receptors [10,11] and as inhibitors of several physiological important enzymes like cyclindependant kinase [12], poly (ADP-Ribose) polymerase [13], urokinase [14] etc.…”
Section: Introductionmentioning
confidence: 99%